First report of predation by a small shark on the invasive rapa whelk Rapana venosa (Valenciennes, 1846) in Argentinean waters - Bonelli, Ana Gabriela (2016)
The rapa whelk Rapana venosa (Valenciennes, 1846) has few predators in areas outside of its native range. Here we report the first incidence of predation by a small shark Mustelus schmitti Springer, 1939 on the rapa whelk in coastal waters of Argentina. This finding could give information about possible trophic control over R. venosa as it potentially disperses into coastal waters of Atlantic South America.